HAT- and HDAC-Targeted Protein Acetylation in the Occurrence and Treatment of Epilepsy - Jie Wang; Feng Yun; Jiahui Sui; Wenpeng Liang; Dingding Shen; Qi Zhang (Biomedicines, 2022)
Epilepsy is a common and severe chronic neurological disorder. Recently, post-translational modification (PTM) mechanisms, especially protein acetylation modifications, have been widely studied in various epilepsy models or patients. Acetylation is regulated by two classes of enzymes, histone acetyltransferases (HATs) and histone deacetylases (HDACs). HATs catalyze the transfer of the acetyl group to a lysine residue, while HDACs catalyze acetyl group removal. The expression of many genes related to epilepsy is regulated by histone acetylation and deacetylation. Moreover, the acetylation modification of some non-histone substrates is also associated with epilepsy. Various molecules have been developed as HDAC inhibitors (HDACi), which have become potential antiepileptic drugs for epilepsy treatment. In this review, we summarize the changes in acetylation modification in epileptogenesis and the applications of HDACi in the treatment of epilepsy as well as the mechanisms involved. As most of the published research has focused on the differential expression of proteins that are known to be acetylated and the knowledge of whole acetylome changes in epilepsy is still minimal, a further understanding of acetylation regulation will help us explore the pathological mechanism of epilepsy and provide novel ideas for treating epilepsy.